Efficacy of 5% Tea Tree Oil Hydrogel on Healing Morbus Hansen's Chronic Plantar Ulcer - Rubianti, Marissa Astari; Ervianti, Evy; Listiawan, Muhammad Yulianto; Indramaya, Diah Mira; Rahmadewi, Rahmadewi; Hendradi, Esti; Prakoeswa, Cita Rosita Sigit (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2021)
Background: The damage of the peripheral nerves that occurs in Morbus Hansen (MH) patients can cause disability due to loss of sensory, motor and autonomic functions can cause wounds, infections, ulcers and disability. Ulcers are the most common cause of disability complications in MH patients and requires a certain time of healing. As many as 10-20% of MH patients experience ulcers on the soles. Tea Tree Oil (TTO) is extracted from steam distillation of the leaves and twigs of the Australian native shrub Melaleuca Alternifolia. In ulcers, TTO can work as an antimicrobial, anti-inflammatory, and antioxidant. TTO preparation in the form of hydrogel is believed to help the wound healing process. Purpose: To investigate the effect of TTO hydrogel 5% on the healing of Chronic Plantar Ulcer of Leprosy (CPUL). Methods: Tea tree oil hydrogel 5% was applied every 3 days for up to 8 weeks in 22 subjects with chronic MH plantar ulcers. Ulcer size, side effects, and possible side effects are evaluated weekly. Result: There were significant clinical and statistical differences in ulcer size (p = 0.000) and in ulcer depth (p = 0.000) after TTO hydrogel 5%. No side effects occurred in this study. The ulcer healed was 59%, the ulcer improved by 36.4%, the persistent ulcer was 4.6%, and there was no ulcer that got worse. Conclusion: TTO hydrogel 5% is effective in the healing process of chronic MH plantar pedis ulcers.